2015
DOI: 10.1002/sim.6377
|View full text |Cite
|
Sign up to set email alerts
|

High‐dimensional propensity score algorithm in comparative effectiveness research with time‐varying interventions

Abstract: The high-dimensional propensity score (hdPS) algorithm was proposed for automation of confounding adjustment in problems involving large healthcare databases. It has been evaluated in comparative effectiveness research (CER) with point treatments to handle baseline confounding through matching or covariance adjustment on the hdPS. In observational studies with time-varying interventions, such hdPS approaches are often inadequate to handle time-dependent confounding and selection bias. Inverse probability weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 65 publications
1
63
0
Order By: Relevance
“…19 The availability of large databases that include detailed clinical data on millions of patients and novel analytic approaches, such as marginal structural models and machine learning, will likely lead to improved risk prediction and prioritization methods in the near future. [20][21][22] It may be difficult, however, to explain these complex statistical approaches to clinicians and patients, who thus may be skeptical of their results.…”
mentioning
confidence: 99%
“…19 The availability of large databases that include detailed clinical data on millions of patients and novel analytic approaches, such as marginal structural models and machine learning, will likely lead to improved risk prediction and prioritization methods in the near future. [20][21][22] It may be difficult, however, to explain these complex statistical approaches to clinicians and patients, who thus may be skeptical of their results.…”
mentioning
confidence: 99%
“…44,45 Schneeweiss et al 46 evaluated a range of algorithms to improve covariate ranking based on the empirical covariate outcome relationship without any meaningful improvement over the ranking using the Bross formula. Ju et al 20 evaluated various choices for the parameters k 1 and k 2 within the hdPS algorithm, and found that the performance of the hdPS was not sensitive to choices for k 1 and k 2 as long as the hyperparameter pair were within a reasonable range.…”
Section: Data Sourcementioning
confidence: 99%
“…In this example we replicate results from the longitudinal data simulation protocol used in two published manuscripts Neugebauer et al (2014, 2015). We first describe the structural equation model that implies the data generating distribution of the observed data, with time-to-event outcome, as reported in Section 5.1 of Neugebauer et al (2015).…”
Section: Simulation Study With Multiple Time Point Interventionsmentioning
confidence: 99%
“…We first describe the structural equation model that implies the data generating distribution of the observed data, with time-to-event outcome, as reported in Section 5.1 of Neugebauer et al (2015). We then show how to specify this model using the simcausal R interface, simulate observed data, define static and dynamic intervention, simulate counterfactual data, and calculate various causal parameters based on these interventions.…”
Section: Simulation Study With Multiple Time Point Interventionsmentioning
confidence: 99%
See 1 more Smart Citation